Determination of the scattered radiation at the neutron calibration laboratory of IPEN using the shadow cone method - ALVARENGA, TALLYSON S. (2018)
Because of the increase in the demand for the calibration of neutron detectors, there is a need for new calibration services. In this context, the Calibration Laboratory of Instituto de Pesquisas Energ??ticas e Nucleares (IPEN), S??o Paulo, which already offers calibration services of radiation detectors with standard X, gamma, beta and alpha beams, has recently projected a new test laboratory for neutron detectors. This work evaluated the contribution of dispersed neutron radiation in this laboratory, using the cone shadow method and a Bonner sphere spectrometer to take the measurements at a distance of 100 cm from the neutron source. The dosimetric quantities ???*(10) and ???p(10) were obtained at the laboratory, allowing the calibration of detectors.